The Effects of Implementing the Eclectic Approach on EFL Learners' Communicative and Linguistic Competencies The Case of Second Year Literature and Philosophy Students in Tahiri Abderrahmane Secondary School -Djelfa - BOUARIF, Cherifa; HAMDOUN ,Nesrine; ROGTI , Maroua (Faculty of Letters and Foreign Languages Department of English, 2019)
Learning English as a foreign language has become one of the most challenging processes due to the significance of this specific language in the world. The drastic prominence given to the English language can be attributed to the immense progression of such a means of communication, and the growing necessity for its implicature in most institutes. However, the means of transmitting knowledge and installing communicative abilities within Algerian EFL learners may still be deficient and ineffective to a certain extent especially that it is centered in motivation and achievement. This study, then, on the implementation of the eclectic approach in Algerian EFL classes, serves as a means towards investigating the effects of using such an approach of language teaching on Algerian EFL learners' motivation and achievement. This aim is based on the assumption that the eclectic approach may add positivity to the process of EFL learning at the levels of motivation and achievement in the classroom. Collecting data required for confirming or infirming the previous hypothesis has been characterized by following an experimental design added to two qualitative instruments that are the questionnaires and observation sheet. The design has been implemented with two samples of teachers and students at the secondary school of Tahiri Abderrahmane. Following the analysis and interpretation of the obtained data, positive deductions have been made confirming that the eclectic approach can benefit Algerian EFL learners in terms of motivation and achievement. Considering these results, some suggestions have been proposed to further research in this area, and attain better results at other levels